Correlation between the serum level of ferritin and D-dimer and the severity of COVID-19 infection - Eman Badawy AbdelFattah; Ashraf Mokhtar Madkour; Shimaa Mohamed I. Amer; Noha Othman Ahmed (The Egyptian Journal of Bronchology, 2023)
Abstract Background Many laboratory biomarkers were used for diagnosis of COVID-19 infection; however, their accuracy to assess the severity and prognosis are still to be evaluated. This study aims to correlate between the serum ferritin and D-dimer levels and the severity of COVID-19 infection and its outcome. Results Retrospective data retrieval of 150 confirmed COVID-19 infection patients admitted in Ain Shams University Specialized Hospital El Obour during period between April and July 2020 were studied. Ninety-six were survivors and 54 were non-survivors. The number of co-morbidities, the level of D-dimer and serum ferritin were correlated with ICU admission, need for mechanical ventilation and mortality with P value < 0.0001. Serum ferritin and D-dimer levels were significantly correlated with degree of HRCT chest severity with P value < 0.0001. The cut-off value of D-dimer for mortality was 700 ng/ml (sensitivity 83.33%, specificity 59.38%), and that for serum ferritin was 300 ng/ml (sensitivity 88.89%, specificity 58.33%), cut-off value of D-dimer for ICU admission was 863 ng/ml and that for serum ferritin was 300 ng/ml, cut-off value of D-dimer for mechanical ventilation was 700 ng/ml, and that for serum ferritin was 600 ng/ml. Conclusion D-dimer and serum ferritin are important biomarkers in predicting the mortality, ICU admission and need for mechanical ventilation in COVID-19 subjects. Thus helps in early detection of risk of progression and improving outcome. The current study also provides probable cut-off values for both biomarkers above which mortality, ICU admission, and mechanical ventilation need can be expected. Trial registration ClinicalTrials.gov ID: NCT0567281. Retrospectively registered. 4th January 2023. https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000CT6C&selectaction=Edit&uid=U00056R5&ts=2&cx=-tlu9xu .